2023
DOI: 10.3389/fpls.2023.1250684
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous myristate promotes the colonization of arbuscular mycorrhizal fungi in tomato

Xiaodi Liu,
Zengwei Feng,
Wei Zhang
et al.

Abstract: Arbuscular mycorrhizal fungi (AMF) can establish symbiotic associations with the roots of most terrestrial plants, thereby improving the tolerance of the host plants to biotic and abiotic stresses. Although AMF cannot synthesize lipids de novo, they can obtain lipids from the root cells for their growth and development. A recent study reveals that AMF can directly take up myristate (C14:0 lipid) from the environment and produce a large amount of hyphae in asymbiotic status; however, the effect of environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
(104 reference statements)
1
1
0
Order By: Relevance
“…Intriguingly, exogenous myristate caused a loss of directional growth in extraradical hyphae towards the roots (tropism) in our study (Fig. 1) and in others’ research (Liu et al ., 2023), suggesting an interruption in the normal signal communication in AM. Notably, the signaling role of myristate has also been found in several soil-borne bacteria (Fernández-Piñar et al ., 2012; Liu et al ., 2024), implying its universal role in regulating the soil microbiome.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Intriguingly, exogenous myristate caused a loss of directional growth in extraradical hyphae towards the roots (tropism) in our study (Fig. 1) and in others’ research (Liu et al ., 2023), suggesting an interruption in the normal signal communication in AM. Notably, the signaling role of myristate has also been found in several soil-borne bacteria (Fernández-Piñar et al ., 2012; Liu et al ., 2024), implying its universal role in regulating the soil microbiome.…”
Section: Discussionsupporting
confidence: 82%
“…However, the extent to which the physiological and ecological responses of AMF to external myristate during the asymbiotic phase mirror those in symbiotic growth, the typical state of AMF in nature, remains unclear. A recent investigation reported that although exogenous myristate does not affect the extraradical biomass of symbiotic AMF, it enhances AMF colonization by stimulating the growth and development of extraradical hyphae (Liu et al ., 2023). To date, the effects of exogenous fatty acid on AM symbiosis and their underlying mechanisms are still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%